Thrombospondin‐1 is part of a Slug‐independent motility and metastatic program in cutaneous melanoma, in association with VEGFR‐1 and FGF‐2. (13th October 2014) - Borsotti, Patrizia; Ghilardi, Carmen; Ostano, Paola; Silini, Antonietta; Dossi, Romina; Pinessi, Denise; Foglieni, Chiara; Scatolini, Maria; Lacal, Pedro M.; Ferrari, Raffaele; Moscatelli, Davide; Sangalli, Fabio; et al.
Summary Differently from most transformed cells, cutaneous melanoma expresses the pleiotropic factor thrombospondin‐1 (TSP‐1). Herein, we show that TSP‐1 (RNA and protein), undetectable in four cultures of melanocytes and a RGP melanoma, was variously present in 13 cell lines from advanced melanomas or metastases. Moreover, microarray analysis of 55 human lesions showed higher TSP‐1 expression in primary melanomas and metastases than in common and dysplastic nevi. In a functional enrichment analysis, the expression of TSP‐1 correlated with motility‐related genes. Accordingly, TSP‐1 production was associated with melanoma cell motility in vitro and lung colonization potential in vivo. VEGF/VEGFR‐1 and FGF‐2, involved in melanoma progression, regulated TSP‐1 production. These factors were coexpressed with TSP‐1 and correlated negatively with Slug (SNAI2), a cell migration master gene implicated in melanoma metastasis. We conclude that TSP‐1 cooperates with FGF‐2 and VEGF/VEGFR‐1 in determining melanoma invasion and metastasis, as part of a Slug‐independent motility program.